Analisis Butir Soal Pengetahuan Dasar Matematika Menggunakan Pendekatan Rasch - L. Parisu, Chairan Zibar; Ekadayanti, Waode; Sisi, La; Juwairiyah, Arna; Kasmawati (Universitas Sarjanawiyata Tamansiswa, 2024)
The analysis of test items is emphasized as the main focus in improving the quality of tests and providing diagnostic information regarding students' understanding. The Rasch approach is chosen as the statistical method to assess the reliability and validity of test items in mathematics exams. This research specifically aimed to analyse the basic mathematics knowledge test items of elementary school students using the Rasch approach, with the goal of producing high-quality test instruments to measure students' basic mathematics knowledge. This study is a quantitative descriptive research with a sample of 75 elementary school students in Kendari. The analysed test instrument consisted of 25 multiple-choice questions and was analysed using the Rasch approach by implementing the Winstep program. The results showed that twenty-four items were valid and one item was invalid. The reliability obtained was categorized as good at 0.94. There were six items classified as the most difficult, seven items as difficult, nine items as easy, and three items as the easiest. As in the item differentiator, one item was categorized as very poor, one as poor, eleven as fair, and twelve as good.